SUSCEPTIBILITY OF YELLOW DWARF COCONUT SEEDLINGS TO Pestalozzia palmarum Cooke - Garcia, Samuel I.; Palomar, Manuel K. (Annals of Tropical Research, 1981)
The average number of leaf spots from natural infection was generally lower than that obtained when Yellow Dwarf coconut seedlings were artificially inoculated with spore suspensions of Pestalozzia palmarum Cooke. It was likewise observed that 200 to 300 spores per drop of inoculum produced the highest number of leaf spot among all the treatments at 37 days after inoculation; 50 to 75 spores per drop of fungal suspension was the minimum concentration of P. palmarum and 100 to 150 spores the optimum that can cause disease infection on a susceptible host plant. The severity and the average rate of increase of leaf spot in every count was linearly correlated with the inoculum concentration from the first count at 21 days until the ninth count at 37 days after inoculation.